The influence of nitrogen and potassium on plant growth and on yield of soybeans planted in winter - de Salvo Soares Novo, Maria do Carmo; Tetsuo Tanaka, Roberto; Antonio Mascarenhas, Hipólito Assunção; Vila Nova Alves Pereira, José Carlos; Bortoletto, Nelson; Boller Gallo, Paulo; Teixeira Vargas, Álvaro Augusto (Pesquisa Agropecuaria Brasileira, 1997)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} @font-face {font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} a:link, span.MsoHyperlink {color:blue; text-decoration:underline; text-underline:single;} a:visited, span.MsoHyperlinkFollowed {color:purple; text-decoration:underline; text-underline:single;} p {margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> An experiment was installed at three Experimental Stations, namely Mococa, Ribeirão Preto and Votuporanga, SP, Brazil, in three different types of soil to study the effect of doses of N and K on soybeans planted in winter. The doses of N used were 0, 50 and 100 kg of N/ha in the form of urea and those of K were 0, 30 and 60 kg of K2O/ha in the form of potassium chloride. The two cultivars of soybeans utilized were IAC-8 and IAC-14. The statistical design was factorial with three replications. The seeds of all treatments were inoculated with the recommended strains of Bradyrhizobium japonicum. At full bloom, the dry matter weight of the roots and the above ground parts were determined as well as the concentration of N and K. Growth of roots and of the above-ground parts was facilitated by the use of nitrogen at Mococa and Votuporanga. Nitrogen increased the soybean yield at the three localities. Potassium did not affect the parameters studied, but there was a preferencial absorption of K by IAC-14 which is very demanding in this element.